A companion to popular culture - Burns, Gary 1952 June 10-
"Includes over two dozen essays covering the spectrum of popular culture studies from food to folklore and from TV to technology"--Provided by publisher.
JB Javier (Recommending faculty) AY 2022-2023
Includes index.
Keywords: Popular culture -- Study and teaching; SOCIAL SCIENCE / Popular Culture